2011
DOI: 10.1093/geront/gnr006
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging Through the eyes of Alaska Native Elders. What It Means to Be an Elder in Bristol Bay, AK

Abstract: This research seeks to inform studies on indigenous aging that prioritizes the perspectives of elders to affect positively on the delivery of health care services in rural Alaska.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 15 publications
7
115
0
Order By: Relevance
“…Involvement with the community provides an opportunity for seniors to pass on cultural knowledge and traditions to youth, which is an important component of cultural continuity. Furthermore, when seniors share teachings and stories with youth, opportunities for engagement are enhanced (Lewis, 2011). It was clear that senior participants were enjoying the benefits of this type of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement with the community provides an opportunity for seniors to pass on cultural knowledge and traditions to youth, which is an important component of cultural continuity. Furthermore, when seniors share teachings and stories with youth, opportunities for engagement are enhanced (Lewis, 2011). It was clear that senior participants were enjoying the benefits of this type of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that, compared to physical and mental health, social connection and support from family and the community make a more significant contribution to seniors' conceptions of successful aging and that this type of connection requires more attention from society [5,6] found that older adults are actually embracing digital gaming contrary to the popular belief that seniors are reluctant to play digital games. The study's results highlight that older adults who play digital games, even occasionally, perform better than elderly non-gamers on some psychological functioning tests (e.g., well-being, affect, depression, and social functioning), which could reflect successful aging.…”
Section: Social Connectednessmentioning
confidence: 99%
“…The role of Elder is distinguished from older adult and constitutes a community and family recognition of the person for their contribution to the group, their cultural knowledge, and their capacity for consultation and advice to others, based upon accumulated wisdom of life experience (Lewis, 2011). Community and family members honor and respect their Elders and this cultural convention distinguishes those who have lived traditionally, engaged in healthy behaviors, taught others, and served as an integral part of their community and served as role models (Lewis, 2011), and thus the reason it is capitalized in this commentary.…”
Section: Cultural Definition Of Aian Eldersmentioning
confidence: 99%